Analyzing ecological security impacts of land use changes through novel landscape ecology metrics and scenario modeling - Y. Moarrab; V. Novin (International Journal of Human Capital in Urban Management, 2025)
ABSTRACT:BACKGROUND AND OBJECTIVES: Rapid urbanization has significantly impacted land use and land cover, disrupting ecosystems and threatening ecological security. This study assessed the ecological security impacts of land use changes in the Lavasanat watershed from 2000 to 2040 using scenario modeling and landscape metrics. Findings show that urban expansion significantly reduces ecological security, with severe impacts under pessimistic scenarios. Sustainable urban planning policies are essential to mitigate these effects.METHODS:  Land use maps for 2000, 2010, and 2020 were created using Landsat imagery and processed with Environment for Visualising Images and Geographic Information System tools. The Markov chain and Cellular Automata-Markov models predicted land use changes to 2040 under current, pessimistic, realistic, and optimistic scenarios with IDRISI software. Landscape metrics, including the number of patches, landscape shape index, interspersion and juxtaposition index, class area, percentage of landscape, and largest patch index, were calculated at class and landscape levels using FRAGSTATS. The Integrated Valuation of Ecosystem Services and Tradeoffs model simulated ecological outcomes for each scenario.FINDINGS: The pessimistic scenario showed a 32% increase in built-up land cover, with an 18% reduction in patch numbers and a 12% decline in landscape shape complexity. Meanwhile, the percentage of built-up land cover rose, forming large patches (the largest patch index rose by 28%). These changes disrupted the watershed’s structure and reduced ecologically valuable areas.CONCLUSION: The findings reveal that urban expansion significantly threatens ecological security, particularly under pessimistic scenarios. This study provides a novel framework for assessing ecological risks by integrating landscape metrics with scenario modeling. The results emphasise the need for sustainable urban planning to mitigate environmental degradation and enhance resilience. Structural landscape changes, including reduced patch complexity and increased fragmentation, were key drivers of ecological decline